The Notion of Eternal Return in Milan Kundera’s The Unbearable Lightness of Being - Shahnewaz Kabir (Crossings, 2011)
Milan Kundera, in his most popular and critically acclaimed novel, The Unbearable Lightness of Being (1984), contemplates on the idea of eternal return devised by Friedrich Nietzsche and the idea of binary opposition between lightness and weight proposed by Parmenides. The novel sets in motion a set of complicated relationships mostly between Tomas, Tereza and Sabina, which are juxtaposed with the duality of lightness and weight based upon the idea of eternal return. Although Parmenides posits that lightness is positive and weight negative, Milan Kundera, in favor of Nietzsche, observes that the heaviest of weights, such as eternal returns, designates the most intense fulfillment in human life. This paper attempts to show that in spite of the deliberate ambiguity we observe in the novel the attainment of meaning can be compared to weight in the terms of Parmenides. Lightness, the binary opposition of weight, is suggestively denounced by the way the novel is developed along with the narratives, being guided by explanatory digressions. The illustration of Tomas designates a gradual shift from the course of lightness to weight and thus attains the Nietzschean doctrine of human greatness through embracing fate even at the cost of severe sufferings. The portrayal of Sabina in contrast with that of Tomas and Tereza implies Kundera’s denouncement of lightness to make a full circle. This essay presents the philosophical backgrou4d of the idea of eternal recurrence followed by a brief sketch of the story. Then it attempts to show how Kundera explores the Nieatzean ideas through the three central characters and their inter–relationships in The Unbearable Lightness of Being.